ANALYSIS OF SUITABILITY LAND FOR FLOOD-FREE SETTLEMENT IN BAOLAN DISTRICT TOLITOLI REGENCY - Ferdi, Ferdi; Saputra, Iwan Alim; Rahmawati, Rahmawati; Budianta, Aziz (GeoEco, 2023)
Baolan District, Tolitoli Regency, as a urban area is quite worrying, because it is often hit by floods. The settlement area is an area that is often affected, because the settlement area of Baolan District is in the vulnerable to very vulnerable class. This research was conducted in Baolan District from April to August 2021. The tools and materials used in this study were: a laptop, ArcGis 10.4 software, and secondary data (rainfall data, DEM data or Digital Elevation Model, soil type maps, and maps). RBI scale 1:50000). This type of research is quantitative descriptive with a spatial approach and using saturated sampling rules obtained from the entire population. The purpose of this study was to determine the distribution and level of suitability of land designated for flood-free settlements in Baolan District. The results of the analysis show that the suitability class that has the largest distribution area is the QS class (Quite Suitable) with an area of 31570.148 or 79.97%. Class S (Suitable) is the class with the smallest area of distribution, which is 538.892 or 1.37%, while the other class is class that is not suitable (N) with an area of 7368.287 or 18.66%. Class S (Suitable) indicates that the class is very wide good if it is developed for a useful area and inversely proportional to class N (Not Suitable). While QS (Quite suitable) is a class that is good enough to be developed into a useful area, but there are several things to consider. the condition of the area is quite steep and the topography is high, as a result it will cause natural hazards such as erosion and land slides. Another thing to consider is the area that covers the rain catchment area which should be predominantly functioned as a buffer zone.